2020
DOI: 10.1136/bmjpo-2019-000620
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Cognitive–behavioural therapy combined with music therapy for chronic fatigue following Epstein-Barr virus infection in adolescents: a feasibility study

Abstract: ​BackgroundCognitive–behavioural therapy (CBT) is effective in chronic fatigue syndrome. However, CBT has not been investigated in postinfectious chronic fatigue (CF), nor is it known whether addition of therapeutic elements from other disciplines might be feasible. We studied the feasibility of a combined CBT and music therapy intervention for CF following Epstein-Barr virus (EBV) infection in adolescents.​MethodsAdolescents (12–20 years old) participating in a postinfectious cohort study who developed CF 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…2586 Following the full text screening, five papers were deemed appropriate to include in the narrative synthesis (further details in figure 1). 13,8790…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2586 Following the full text screening, five papers were deemed appropriate to include in the narrative synthesis (further details in figure 1). 13,8790…”
Section: Resultsmentioning
confidence: 99%
“…However, they noted that the study was underpowered and recommended the trial should be treated as an exploratory study as sufficient power is needed to assess the effectiveness of this treatment modality. 13…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pilot trial of physical exercise, which compared two variations (aerobic and resistance training), within a multicomponent inpatient programme (including physiotherapy, occupational therapy and psychological therapy), found that both variations led to improvements in quality of life, but only aerobic training decreased fatigue severity (Gordon et al, 2010). Music therapy has been combined with CBT and has been found to be feasible and acceptable, with indications of favourable outcomes in adolescents with postinfectious chronic fatigue (Malik et al, 2020).…”
Section: Treatmentmentioning
confidence: 99%